1997
DOI: 10.1074/jbc.272.43.27140
|View full text |Cite
|
Sign up to set email alerts
|

Transport of Rat Liver Glycine N-Methyltransferase into Rat Liver Nuclei

Abstract: Rat liver cytosolic glycine N-methyltransferase (GNMT) catalyzes the S-adenosylmethionine-dependent methylation of glycine to sarcosine. It is comprised of four identical 292-amino acid residue subunits. Recently, evidence has been provided to show that GNMT is identical to the cytosolic receptor for benzo[a]pyrene, which induces cytochrome P450 1A1 gene expression. In the present study we show that chemical modification of purified rat liver GNMT with fluorescein isothiocyanate (FITC) resulted in dissociation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 34 publications
0
13
0
1
Order By: Relevance
“…coli and purified by several subsequent chromatographic steps as we previously described [14]. Site-directed mutagenesis was carried out using a QuickChange site-directed mutagenesis kit (Stratagene) and confirmed by DNA sequencing of the mutant constructs at the Nucleic Acid Analysis Core Facility, MUSC.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…coli and purified by several subsequent chromatographic steps as we previously described [14]. Site-directed mutagenesis was carried out using a QuickChange site-directed mutagenesis kit (Stratagene) and confirmed by DNA sequencing of the mutant constructs at the Nucleic Acid Analysis Core Facility, MUSC.…”
Section: Methodsmentioning
confidence: 99%
“…Although each of the four subunits has a catalytic center, the structural organization of the enzyme as a tetramer is important for its catalytic activity. In fact, GNMT dimers or monomers are catalytically inactive [12,14]. The oligomeric structure of the enzyme is also important for its regulation by folate since the GNMT tetramer binds only two molecules of 5-methyltetrahydrofolate (5-MTHF).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…GNMT, which is primarily expressed in cell cytoplasm (6,9,20), is a polycyclic aromatic hydrocarbon-binding protein (27). Previously, we and other groups showed that if the cells were treated with benzo(a)pyrene, GNMT will be translocated into the nuclei (8,28,29). Because cigarette smoking has been identified as a possible prostate cancer risk factor and GNMT inhibits benzo(a)pyrene-7,8-diol-9,10-epoxide-DNA adduct formation (8), the GNMT expression in the prostate may exert a protective effect for individuals exposed to benzo(a)pyrene and its down-regulation may be an early sign for prostate cancer carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have questioned the role of GNMT as the 4 S aryl hydrocarbon receptor (8). Studies in which GNMT was incubated with isolated rat liver nuclei showed that native tetrameric GNMT was unable to enter the purified liver nuclei (10). The possible function of GNMT in the nucleus is still a matter of speculation, and if GNMT in the nucleus is not simply a result of cytoplasmic contamination, its function there is not clear because it does not appear to be involved in the induction of the cytochrome P-450 family of enzymes.…”
Section: Gnmt Genes and Proteinsmentioning
confidence: 99%